Respectful encounters and return to work: empirical study of long-term sick-listed patients' experiences of Swedish healthcare - Lynöe, Niels (BMJ Group, 2011)
AIMS: To study long-term sick-listed patients' self-estimated ability to return to work after experiences of healthcare encounters that made them feel either respected or wronged. METHODS: A cross-sectional and questionnaire-based survey was used to study a sample of long-term sick-listed patients (n=5802 respondents). The survey included questions about positive and negative encounters as well as reactions to these encounters, such as ‘feeling respected’ and ‘feeling wronged’. The questionnaire also included questions about the effects of these encounters on the patients' ability to return to work. RESULTS: Among patients who had experienced positive encounters, those who also felt respected (n=3327) demonstrated significantly improved self-estimated ability to return to work compared to those who did not feel respected (n=79) (62% (95% CI 60% to 64%) vs 34% (95% CI 28% to 40%)). Among patients with experiences of negative encounters, those who in addition felt wronged (n=993) claimed to be significantly more impeded from returning to work compared to those who did not feel wronged (n=410) (50% (95% CI 47% to 53%) vs 31% (95% CI 27% to 35%)). CONCLUSIONS: The study indicates that positive encounters in healthcare combined with feeling respected significantly facilitate sickness absentees' self-estimated ability to return to work, while negative encounters combined with feeling wronged significantly impair it.